2018
DOI: 10.1177/1753193418817968
|View full text |Cite
|
Sign up to set email alerts
|

Failed peripheral nerve reconstruction with processed nerve allografts in three patients

Abstract: References Laing T, Siddiqui A, Sood M. The management of neuropathic pain from neuromas in the upper limb: surgical techniques and future directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…In our study, allografts with diameters of up to 5 mm were used and the poorest outcomes were seen in larger diameter grafts, with > 3 mm in diameter appearing to be inhibitory to axonal regeneration. Best et al (53) demonstrated that in large diameter nerve grafts, scar formation as a sequelae to central ischaemia develops; this is likely to be the case with our results and has recently been reported in three cases (54). However, in comparison to autologous nerve grafts, the allograft is perhaps more sensitive.…”
Section: A C C E P T E Dsupporting
confidence: 75%
“…In our study, allografts with diameters of up to 5 mm were used and the poorest outcomes were seen in larger diameter grafts, with > 3 mm in diameter appearing to be inhibitory to axonal regeneration. Best et al (53) demonstrated that in large diameter nerve grafts, scar formation as a sequelae to central ischaemia develops; this is likely to be the case with our results and has recently been reported in three cases (54). However, in comparison to autologous nerve grafts, the allograft is perhaps more sensitive.…”
Section: A C C E P T E Dsupporting
confidence: 75%
“…Nietosvaara et al presented three cases of PNAs ranging from 20 mm to 50 mm failing to facilitate any measurable axon regeneration across these PNAs. In fact, they document that the PNAs resorbed leaving behind scar tissue, and in one case, had thickened into a neuroma‐like stump . Overall, this evidence is perhaps the strongest reason to take a conservative approach to using alternatives in the clinic until these circumstances are better understood.…”
Section: Guidelines For Nerve Graft Repairsmentioning
confidence: 99%
“…Recent clinical investigations suggest processed nerve allografts may provide an alternative to autograft for segmental defects of motor or mixed motor/ sensory nerves (Leckenby et al, 2020;Safa et al, 2019). Despite their increasing popularity, experience with allograft failure is limited and mainly based on animal experiments and case reports (Nietosvaara et al, 2019;Saheb-Al-Zamani et al, 2013). A common finding is central necrosis with intraneural fibrosis and insufficient axonal regeneration.…”
Section: Problem Statementmentioning
confidence: 99%